Criteria for a nursing curriculum for the new millennium - Louise De Villiers (AOSIS, 1999)
This article is based upon literature research aimed at theorising about a curriculum development model for the Programme leading to Registration as a Nurse (General, Psychiatric and Community) and Midwife. Opsomming Die artikel is gebaseer op literatuumavorsing gerig op teoretisering oor 'n kurrikulumontwikkelingsmodel vir die Program vir Registrasie as 'n Verpleegkundige (Algemene, Psigiatriese, Gemeenskaps-) en Vroedvrou. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.